PENGARUH KOMPETENSI PROFESIONAL GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN MODERASI SUPERVISI KEPALA SEKOLAH DI SMA NEGERI KECAMATAN PATI - Dyah Retno Nugraheni, 12.52.02.0197; Suhari, Yohannes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to: (1) to analyze the influence of the professional competence of teachers on teacher performance in upper secondary schools in the District Pati; (2) to analyze the effect of work motivation on the performance of teachers in upper secondary schools in the District Pati; (3) analyze the effect of the principals supervision of the performance of teachers in upper secondary schools in the District of Pati. This research is quantitative research. The population in this study are all teachers in secondary schools in the District Pati totaling 164 people. Samples taken in the census. The instrument used for data collection was a questionnaire using a Likert scale, each of which has qualified the validity and reliability of the factor analysis and AlphaCronbach and test Classical Assumption. Data analysis techniques using test models of multiple linear regression analysis. R2 test, F test, and hypothesis testing using t test. The results showed that: (1) Teachers Professional Competence positive and significant impact on teacher performance teacher at SMA District of starch; (2) Work motivation positive and significant effect on Teacher Performance in SMA District of starch; (3) Supervising Principal positive and significant effect on the performance of teachers in SMA District of starch; (4) Supervising Principal moderate the influence of teacher professional competence in a positive and significant impact on the performance of teachers in SMA District of starch; (5) Supersivi Principal Motivation moderate work on teacher performance in SMA District of Pati. Keywords: teachers professional competence, motivation, supervision of the principal, and teacher performanc